2007
DOI: 10.1007/s10661-007-9987-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and filter-based measurements of PM2.5 nitrate and sulfate at the Fresno Supersite

Abstract: PM(2.5) nitrate (NO-(3)) and sulfate (SO=(4)) were measured continuously with R&P8400N and R&P8400S instruments, respectively, and compared with filter-based measurements at the Fresno Supersite from October, 2000 through December, 2005. NO-(3) concentrations were higher in winter than summer with a long-term decreasing trend. Correlations between 24-h average continuous and filter-based NO-(3) were greater than 0.96 in 4 out of 5 years. Continuous NO-(3) was generally lower than filter-based NO-(3) although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
(35 reference statements)
1
18
0
1
Order By: Relevance
“…This effect has been attributed to incomplete volatilization and/or incomplete catalytic conversion of NO − 3 to NO. Two identical instruments at the Fresno supersite yielded data that were also well correlated but different by 10-55 % in the annual average (Chow et al, 2008). As a result, we treat these observations as uncalibrated but internally consistent over time.…”
Section: A1 Long-term Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has been attributed to incomplete volatilization and/or incomplete catalytic conversion of NO − 3 to NO. Two identical instruments at the Fresno supersite yielded data that were also well correlated but different by 10-55 % in the annual average (Chow et al, 2008). As a result, we treat these observations as uncalibrated but internally consistent over time.…”
Section: A1 Long-term Recordsmentioning
confidence: 99%
“…There data were collected in Fresno in -2001(Watson et al, 2000 as part of the EPA PM Supersites program (http://www.epa.gov/ttnamti1/ supersites.html). These measurements were made by flash volatilizing NH 4 NO 3 , reducing HNO 3 across a heated catalyst to nitric oxide (NO), and detecting NO by chemiluminescence (Stolzenburg et al, 2003;Chow et al, 2008). It was reported that 24 h averages of these high-time-resolution observations were well correlated with, but 20-40 % lower than, 24 h PM 2.5 filter samples (annual averages).…”
Section: A1 Long-term Recordsmentioning
confidence: 99%
“…The OC or OC mass (OCM) estimated from the material balance can be compared with those measured from quartz fiber filters using different multipliers to evaluate other artifact correction methods. This assumes that other semi-volatile species (e.g., ammonium nitrate [47][48][49][50] ) are accounted for in the material balance. This approach provides a basis to evaluate artifact correction methods and to estimate the OC artifact in PM 2.5 mass.…”
Section: Regression Intercept Approachmentioning
confidence: 99%
“…The PM 2.5 fraction is dominated by ammonium nitrate and carbonaceous aerosol during fall and winter. Sulfur dioxide emissions in the SJV are low (CARB, 2012), but oxides of nitrogen and ammonia emissions are high (Mansell and Roe, 2002), so lower temperatures and higher relative humidities during late fall and winter favor ammonium nitrate formation (Stockwell et al, 2000;Chow et al, 2005b;Lurmann et al, 2006;Chow et al, 2008). PM 2.5 carbonaceous aerosol in the SJV derives from engine exhaust, biomass burning, cooking, and conversion of organic gases to particles (Chow et al, 1992;Strader et al, 1999;Schauer and Cass, 2000;Chow et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%